SUPPLEMENT USE AND GASTROINTESTINAL BLEEDING - B. ZEICHNER, SIMON; CAVALCANTE, MILENA; A.BARKIN, JAMIE (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The use of supplements, such as vitamins, over the counter (OTC) agents, and herbal remedies have become a popular complementary therapy for a variety of conditions. There have been case reports describing an increased risk of bleeding associated with these supplements. Our objective was to test the hypothesis that there is an increased incidence of gastrointestinal bleeds among patients who take supplements. Methods This was a prospective cohort, survey-based study of 100 patients seen at MSMC from February 2013 to August 2013. Data included patient age, sex, ethnicity, country of origin, alcohol use, medical comorbidities, information regarding previous gastrointestinal (GI) bleeds, laboratory values, as well as the use of supplements, multivitamins, and anticoagulants. Results Overall, 32% of patients who had gastrointestinal bleeding consumed supplements. More patients in the supplement group took NSAIDS 52.9% vs. 27.9%, p =0.07), whereas more patients in the no supplement group took the combination of ASA and clopidogrel (25.6% vs. 5.9%, p = 0.08). Patients in the supplement group were less likely to have an elevated international normalized ratio (INR between 1.3-2.0: 6.3% vs. 22.1%, p = 0.05). Patients not taking supplements were significantly more likely to have no intervention done (14.7%) vs. 0%, p = 0.02). Conclusion Supplement use within the community is very common. Although non-significant, patients taking supplements appeared to have more severe gastrointestinal bleeds that required more interventions. Larger studies are needed to better define the risks of GI bleeding with particular supplements. Â Keywords: alternative medicine; gastrointestinal bleeding; herbal supplements